A cascading reaction by hydrological spatial dynamics alternation may be neglected. (1st August 2022) - Hao, Ying-Ying; Zhao, Bin; Wu, Wan-Ben; Zheng, Jun-Yi
Abstract: Water regime changes play a critical role in the structure and function of watershed ecosystems. However, most previous studies focused only on static fixed-point quantitative change at a given time, ignoring the hydrological spatial distribution states of wetting and drying and lacking dynamic indicators for characterization. Here, we constructed a new dynamic index to characterize water alternation of wetting and drying of Poyang Lake, the largest freshwater lake in China, using all available Landsat images and Google Earth Engine from 1987 to 2020. In addition, we analyzed the relative contribution of the dam to water regime changes according to geographical characteristics, and a neglected cascading reaction was found between the upstream and downstream of the basin. The results showed that the alternation of Poyang Lake significantly intensified, and varied with different years. Although the apparent regulation of the Three Gorges Dam (TGD) has no significant impact on the maximum storage of the downstream Poyang Lake and the runoff of the further Yangtze Estuary, the TGD has changed the water spatial alternation of Poyang Lake, resulting in a cascading reaction to the runoff of the Yangtze Estuary.